Kinerja Guru pada Lembaga Pendidikan Islam Perspektif Performance Management - Ine Ratu Fadliah; Rena Andini (Universitas Muhammadiyah Jakarta, 2026)
Teacher performance in Islamic educational institutions continues to face significant challenges, particularly due to unsystematic management practices, the dominance of administrative approaches, and the lack of integration of Islamic values within performance evaluation systems. This study aims to analyze teacher performance from a performance management perspective and to formulate an integrative and contextual conceptual model. The research employs a qualitative approach using library research, with the researcher as the primary instrument (human instrument) supported by a literature analysis matrix. The research subjects consist of academic documents such as books, journal articles, and other relevant scholarly works selected purposively based on credibility and relevance. Data were collected through documentation and systematic literature review, and analyzed using content analysis and conceptual synthesis. The findings indicate that teacher performance has not been managed within a comprehensive performance management cycle, and a gap remains between theoretical concepts and practical implementation. This study proposes a teacher performance model that integrates planning, implementation, evaluation, and development with Islamic values such as amanah, ihsan, and moral responsibility. In conclusion, the integration of modern performance management with Islamic educational values enhances the effectiveness, quality, and holistic meaning of teacher performance].